Socioeconomic differences in obesity among Mexican adolescents - ULLMANN, S. HEIDI (2010)
OBJECTIVE: We investigate socioeconomic disparities in adolescent obesity in Mexico. Three questions are addressed. First, what is the social patterning of obesity among Mexican adolescents? Second, what are the separate and joint associations of maternal and paternal education with adolescent obesity net of household wealth? Third, are there differences in socioeconomic status (SES) gradients among Mexican boys and girls, rural residents and non-rural residents? METHODS: Using data from the Mexican National Health Survey 2000 we examined the slope and direction of the association between SES and adolescent obesity. We also estimated models for sub-populations to examine differences in the social gradients in obesity by sex and non-rural residence. RESULTS: We find that household economic status (asset ownership and housing quality) is positively associated with adolescent obesity. High paternal education is related to lower obesity risk, whereas the association between maternal education and obesity is positive, but not always significant. CONCLUSION: The household wealth components of SES appear to predispose Mexican adolescents to higher obesity risk. The effects of parental education are more complex. These findings have important policy implications in Mexico and the United States.